Evaluation Implementation Of Regional Program Empowering “Gotong Royong” In New Autonomy Region - Abdulkadir, Judhi Ichtiyar; Madhakomala, R.; Idris, Fahmi (International Journal of Scientific Research and Management (IJSRM), 2018)
This research aims to illustrate the success of a program. The Stufflebeam CIPP Evaluation Model with the view that the most important goal of evaluation is not proving but to improve. And has been the program of Regional Empowerment of “Gotong Royong” (Mutual Cooperation), is an empowerment program; and as a complex function of community management, governance involves relationships between the various forces within the State in the region of local government, civil society, economic society and political society. Empowerment that prioritizes the importance of participation of all societies, to participate actively from the planning stage to the stage of evaluation, and development (bottom-up planning). This mechanism of community empowerment aims to accelerate the prevention of society that bears the Predicate of Social Welfare Problems. Poverty and one of the principles of governance is the network. West Sumbawa Regency as a New Autonomous Region, thereby governance when the authority is decentralized to power centers of many people / groups / institutions, where one another controls (checks and balances) to then build collaboration and network of activities that support each other in an integrated design team (IDT). Some of the indicators used in this study are targeted beneficiaries, community participation, and benefits received by the community. Based on the observations in the field and data processing obtained that first; for beneficiary target indicators, the most beneficiaries of the PoSWP are the poor in the sector; Micro, Agriculture, Livestock, and Fishery & Marine. Second; Indicator of community participation, obtained by category in medium participation. Third; for the benefit indicator received, it was found that the benefits of the skills, knowledge, health, and income received by the village community were categorized in the moderate rise category.